Long-term impact of positive surgical margins on biochemical recurrence after radical prostatectomy: Ten years of follow-up. (April 2014) - Rouanne, Mathieu; Rode, Julie; Campeggi, Alexandre; Allory, Yves; Vordos, Dimitri; Hoznek, Andras; Abbou, Claude-Clement; La Taille, Alexandre De; Salomon, Laurent
Abstract Objective. Positive surgical margins (PSMs) in men undergoing radical prostatectomy (RP) for prostate cancer are associated with an increased risk of biochemical recurrence. This study evaluated the long-term (>10 year) impact of PSMs on biochemical recurrence after RP in adjuvant treatment-naïve pT2–pT4 N0 men and determined predictors of prostate-specific antigen (PSA) failure. Material and methods. The institutional registry of 1276 patients who underwent RP at Henri Mondor Hospital from 1988 to 2001 was reviewed, identifying 403 patients with regular follow-up at the time of analysis. The study included 108 patients with PSMs who did not receive neoadjuvant or adjuvant therapy before PSA relapse. Median follow-up was 12.2 years. PSA failure was defined by a PSA rising by more than 0.2 ng/ml and biochemical recurrence-free survival (RFS) was estimated using the Kaplan–Meier method. Cox proportional hazard regression models were used to analyse clinicopathological variables associated with biochemical recurrence. Results. Biochemical recurrence 10 years after RP was 33.5% for patients regardless of the margin status. The 10-year biochemical RFS was 73% in men with negative margins compared to 49% in the case of PSM (p < 0.001). In multivariate analysis, margin status was a significantly predictive for PSA failure (hazard ratio 1.46, p = 0.04). After stratification by pathological stage, margin status was significantly predictive for biochemical RFS in pT2 (p < 0.001) and pT3a (p < 0.001), whereas the impact of PSM did not reach significance in pT3b (p = 0.16). Conclusions. After 10-year follow-up, PSMs remain an independent risk factor of biochemical RFS after RP with less relevant impact in pT3b disease. Randomized prospective trials are needed to determine the place of adjuvant versus delayed radiotherapy.